BOOK REVIEW: Radu Vădeanu, „Catalogul absenților. Condamnări politice ale Tribunalului Militar Cluj între anii 1956-1964”, Cluj-Napoca, Mega, 2022, 589 p. - DĂLĂLĂU, Andrei (Studia Universitatis Babeș-Bolyai Historia, 2022)
One of the most famous quotes attributed to Joseph Stalin, although initially enounced in 1932 by German journalist and writer Kurt Tucholsky, says: “The death of one man is a tragedy. The deaths of millions are a statistic”. Regardless of its real or fictional author, the cynic statement refers to the horrors of totalitarian repression that was able to dehumanize the tragedy of millions of human losses. By indexing depersonalized destinies in never-ending lists of names, codes, or aliases, totalitarian authorities collapsed all the emotion, suffering, and tribulation of life stories under one cold and empty unit of analysis: numbers. However, one author decided to bring the statistics back to life to understand victimhood and state repression in the late 1950s and early 1960s in communist Romania. Catalogul absenților (The Absentees’ Catalogue) is Radu Vădeanu’s most recent book, published in 2022 at Mega Publishing House from Cluj-Napoca, Romania. The oxymoron contained in the title reflects the sole purpose of the author’s endeavour: indexing the absentees of history who were persecuted, accused, and then imprisoned for fictitious guilts under various accusatory narratives constructed by the Securitate, prosecutor’s office, and Military Courts.